Storytelling and the use of Aklatang Pambata - Omones, Angelicum R. (2010)
This paper was one group experimental study that tried to prove that storytelling motivates the children not only to enter their community library but also to browse and read books. The study consists of dependent and independent variables that were patterned from Steven's Classification. The independent variable which is the one controlled or manipulated by the experimenter is storytelling. The dependent variables or the variables that serve as measures of the behavior of the subject that reflect the effects of independent variable are the number of children who entered the library and the number of books that they browsed and read.